Early buddhist art of China and Central Asia, volume two : The Eastern Chin and sixteen kingdoms period in China and Tumshuk,Kucha and Karashahr in Central Asia : illustrations. - Rhie, Marylin Martin. (Leiden)
2.c. (lviii s., 18 res., [606] s.)